Analysis of Internal Control over Financial Reporting on Inventory Accounts: A Case Study at Institution X - Putri, Ni Luh Putu Ayu Priscilla Wirantika; Setyaningrum, Dyah (E-Jurnal Akuntansi, 2025)
The implementation of Internal Control over Financial Reporting (PIPK) at Institution X from 2022 to 2024 was deemed effective, yet it does not fully reflect the actual condition, as repeated audit findings from the Audit Board of the Republic of Indonesia (BPK RI) revealed weaknesses in inventory internal control. This indicates that the PIPK design remains suboptimal and requires further analysis in accordance with Minister of Finance Regulation (PMK) Number 17 of 2019. This study employed a qualitative case study approach through document analysis and semi-structured interviews with eight internal respondents and two from the Institution of Finance, using data triangulation to strengthen validity. The results show that the inventory financial reporting process is not fully documented and that risk identification remains limited to areas with existing control tests. Therefore, an integrated flowchart between financial reporting and inventory management, along with extended risk identification, is needed to strengthen the PIPK design. This study contributes by proposing a regulation-based PIPK design to enhance the effectiveness of PIPK and the accountability of financial reporting.  Keywords: Financial Reporting, PIPK Design, Inventory, Internal Control, Ministries/Agencies